2021
DOI: 10.1177/10983007211000381
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Secondary Teachers’ Actual and Perceived Praise and Reprimand Use

Abstract: The present study aimed to identify a way for educators to improve the accuracy of their praise and reprimand reflections to ultimately improve their ability to set, monitor, and evaluate their use of praise and reprimand. To do this, teachers’ natural use of praise and reprimand (in the absence of intervention) were compared with their perceived use. A 20-min direct observation was collected from 66 middle and high school teachers to obtain praise and reprimand rates. Following the observation, teachers repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Data were analyzed as part of a larger study that examined secondary teachers’ actual and perceived use of praise and reprimand (Floress, Beaudoin, et al, 2021). Data were collected before the COVID-19 pandemic over the course of four academic semesters (i.e., fall 2016–spring 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were analyzed as part of a larger study that examined secondary teachers’ actual and perceived use of praise and reprimand (Floress, Beaudoin, et al, 2021). Data were collected before the COVID-19 pandemic over the course of four academic semesters (i.e., fall 2016–spring 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Secondary students may also present unique behavioral challenges, which could influence teachers’ use of praise and reprimand. For example, (Floress, Beaudoin, et al, 2021) found that middle school teachers used significantly higher rates of reprimand than high school teachers, which may relate to middle school teachers dealing with more challenging student behavior.…”
Section: Positive Behavior Intervention Supportsmentioning
confidence: 99%
“…An archival data set from a study (Floress, Beaudoin et al, 2021) examining teachers’ natural use of praise and reprimand was used for this study. This study was reviewed by the Institutional Review Board at Eastern Illinois University and met exemption criteria for human subject research.…”
Section: Methodsmentioning
confidence: 99%
“…Although researchers have identified important features of praise delivery, secondary teachers use more general praise (0.14 per min, once per 8 min) than BSP (0.01 per min, once per 30 min) and use both less often than reprimands (0.20 per min, once per 5 min; Floress et al, 2022). Secondary teachers may be reluctant or unable to use BSP due to inadequate training and misconceptions about the utility of using BSP with older students.…”
Section: Bsp In Secondary Classroomsmentioning
confidence: 99%